An Update on Safe Anticoagulation - Mailer, Reiner K.; Kuta, Piotr; Renné, Thomas (Hämostaseologie, 2022)
Blood coagulation is essential to maintain the integrity of a closed circulatory system (hemostasis), but also contributes to thromboembolic occlusion of vessels (thrombosis). Thrombosis may cause deep vein thrombosis, pulmonary embolism, myocardial infarction, peripheral artery disease, and ischemic stroke, collectively the most common causes of death and disability in the developed world. Treatment for the prevention of thromboembolic diseases using anticoagulants such as heparin, coumarins, thrombin inhibitors, or antiplatelet drugs increase the risk of bleeding and are associated with an increase in potentially life-threatening hemorrhage, partially offsetting the benefits of reduced coagulation. Thus, drug development aiming at novel targets is needed to provide efficient and safe anticoagulation. Within the last decade, experimental and preclinical data have shown that some coagulation mechanisms principally differ in thrombosis and hemostasis. The plasma contact system protein factors XII and XI, high-molecular-weight kininogen, and plasma kallikrein specifically contribute to thrombosis, however, have minor, if any, role in hemostatic coagulation mechanisms. Inherited deficiency in contact system proteins is not associated with increased bleeding in humans and animal models. Therefore, targeting contact system proteins provides the exciting opportunity to interfere specifically with thromboembolic diseases without increasing the bleeding risk. Recent studies that investigated pharmacologic inhibition of contact system proteins have shown that this approach provides efficient and safe thrombo-protection that in contrast to classical anticoagulants is not associated with increased bleeding risk. This review summarizes therapeutic and conceptual developments for selective interference with pathological thrombus formation, while sparing physiologic hemostasis, that enables safe anticoagulation treatment.
Keywords: coagulation; thrombosis; contact activation; polyphosphate; factor XII